1989
DOI: 10.1051/apido:19890104
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sublethal exposure to diazinon, carbaryl and resmethrin on longevity and foraging in Apis mellifera L

Abstract: Summary — Topical, sublethal applications of three insecticides, diazinon, carbaryl and resmethrin, were given to worker honey bees (Apis mellifera L.) of two age groups, 0 and 14 days. For newly emerged workers, carbaryl was the most hazardous in sublethal amounts, adversely affecting both longevity and foraging age. Resmethrin was intermediate in effect, and diazinon the least hazardous. This is different from mortality studies in which the effects of carbaryl and diazinon were similar, and resmethrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

1994
1994
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
0
6
2
Order By: Relevance
“…Ninety percent of carbaryl detections concerned the samples collected in 2008, which is consistent with the ban on the use of this compound in November 2008 in France, and confirmed that the beehive matrices are very sensitive in terms of reflecting agricultural practices and pesticide use. In addition, it was previously demonstrated that sublethal exposure to carbaryl has adverse effects on the longevity and foraging activities of honey bees [62]. Although the concentrations determined in the present study were lower than those in this semi-field study, chronic exposure to this insecticide might cause problems to bee colonies.…”
Section: Discussioncontrasting
confidence: 67%
“…Ninety percent of carbaryl detections concerned the samples collected in 2008, which is consistent with the ban on the use of this compound in November 2008 in France, and confirmed that the beehive matrices are very sensitive in terms of reflecting agricultural practices and pesticide use. In addition, it was previously demonstrated that sublethal exposure to carbaryl has adverse effects on the longevity and foraging activities of honey bees [62]. Although the concentrations determined in the present study were lower than those in this semi-field study, chronic exposure to this insecticide might cause problems to bee colonies.…”
Section: Discussioncontrasting
confidence: 67%
“…These findings coincide with what has been reported in the literature for carbaryl and other insecticides. For example, bees treated with a LD 5 of diazinon, carbaryl, and resmethrin lived between 7% and 25% shorter lives than control bees (Mackenzie and Winston, 1988). Also, Wu et al (2011) found that adult longevity decreased 4d in bees exposed to residues of imidacloprid, clothianidin, and aldicarb in contaminated brood comb during development, although compared to our study, Wu et al (2011) used doses that were at least five times higher than those used by us for clothianidin and imidacloprid.…”
Section: Honey Bee Survivorshipcontrasting
confidence: 78%
“…Worker bees were challenged orally and topically with sublethal doses of clothianidin, imidacloprid, and carbaryl. In previous studies, sublethal doses of pesticides tested were 5 × 10 0 to 1.5 × 10 2 times lower than their LD 50s (Decourtye et al, 2004;Aliouane et al, 2009), or the LD 5 , LD 10 and LD 25 values (Mackenzie and Winston, 1988). Based on that range of options, in the current study, LD 5 was selected for the sublethal dose to be tested (Table 1).…”
Section: Experiments 1: Effect Of Sub-lethal Doses Of Insecticides On mentioning
confidence: 99%
“…Several neurotoxic insecticides have been shown to have effects on various aspects of foraging behaviour in free‐flying bees. Thus, it has been reported that parathion disrupted the communication dance of foraging bees,16, 17 diazinon affected the onset and the duration of foraging, and the handling of nectar,18 and permethrin and deltamethrin induced an abnormal behaviour pattern during the homing flight 19. 20 The PER assay has also been used to assess the effects of insecticides 21–24.…”
Section: Introductionmentioning
confidence: 99%